ASPECTS REGARDING THE ENERGITICAL VALORIFICATION OF URBAN SLUDGE TREATMENT - DANA-CLAUDIA FARCAȘ-FLAMAROPOL; ELENA SURDU; ION DURBACĂ; ANDREEA NIȚU; RAMONA MARE; EUGEN DUȚU (Journal of Engineering Studies and Research)
This paper highlights through the issues addressed, the application aspects regarding the approach of the concept of recovery of sewage sludge from an urban wastewater treatment plant (SEAU), which is in a stage of technological expansion and modernization. Thus, it is considered the need to process the potential of biological mass generated by anaerobic stabilization in the SEAU, with a population of about 10,000 equivalent inhabitants, which requires on one hand, the technological design of activated sludge basins and on the other hand, the design of a sewage sludge fermentation tank, in order to produce biogas, necessary for its recovery for energy purposes.